INVESTIGASI PEMBENTUKKAN IKATAN Zn-O RODS DI ATAS PERMUKAAN MIKROKANTILEVER DENGAN UJI KARAKTERISASI FTIR - Mia Yuliana Frestika; Rina Dewi Mayasari; Masmui Masmui; Agustanhakri Agustanhakri; R. Ibrahim Purawiardi; Yuliasari Yuliasari; Ahmad Novi Muslimin; Muhammad Dani; Agus Setyo Budi; Ratno Nuryadi (Spektra: Jurnal Fisika dan Aplikasinya, 2017)
In this work, ZnO (Zinc Oxide) rods, which is a sensitive material for gas detection, are grown on a microcantilever surface by hydrothermal technique. Synthesis of ZnO rods consists of two processes, i.e., a formation of seed layer using Zinc Acetate Dihydrate by a dip-coating and a growth of the ZnO rods using Zinc-Nitrate-Tetrahydrate at a temperature 95Ã‚Â°C for time variations of 2 hours, 4 hours and 6 hours. Drying condition for both seed layer and growth of ZnO rods was done at a temperature of 120 oC for 2 hours. The ZnO rods were then characterized by Fourier Transform Infrared (FTIR) in order to investigate the formation of Zn-O bond. The characterization results indicate that the metal oxide correlation is shown in the wavenumber spectrum of 540 cm-1 for a sample with 2-hour growth time, while the wavenumber spectrum of 548 cm-1 and 547 cm-1 for the growth time of ZnO rods for 4 hours and 6 hours. Wavenumber spectrum approximately at 540-548 cm-1 is predicted to be the absorption of the formation of a Zn-O bond. Keyword: Microcantilever, ZnO rods, dip-coating, hydrothermal, growth time dependent.